A VISUAL ANALYSIS OF STRUCTURAL CLADDING IN THE UNIVERSITY OF LAGOS, AKOKA - Akinde, Dr. Toyin Emmanuel; Odeniyi, Akinkunmi Olatunbosum; Balogun, Temitope Toluwalase; Lawuyi, Funmilayo Dorcas; Elebute, Pita Tireni (Acitya Wisesa: Journal of Multidisciplinary Research, 2025)
University of Lagos (UniLag) is synonymous with the municipality of Akoka. It is Nigeria's most cosmopolitan citadel of higher learning, established in 1962 alongside Universities in Nsukka, Zaria, and Ile-Ife, respectively. Her location in Akoka, which implies primacy in Yoruba philology, can be likened to divine providence or coincidence. Little wonder why the institution pitched itself as “The University of First Choice and the Nation’s Pride" and its product "Akokite". This claim resonates beyond its student enrollment, staff strength, and academic visibility but is typified in architectural structures. Prevalent among such structures are the main gate, the senate house, the library, students' halls of residence, and lecture halls. Interestingly, many of these structures are adorned with cladding; suspended wall finishing, exemplified in paint, wallpaper, flex, wood, metal, stone, marble, glass, and plastic. Regrettably, there is an apparent dearth of literature on the institution’s structural cladding, which supposedly is an oversight or oversimplification of its finishing and aesthetic roles. This research aims to highlight all that constitutes cladding on the Akoka campus of UniLag. As such, the study attempts visuality of Akoka structures, sixteen (16) of which were purposely shortlisted from the pool, each attests cladding representation of diverse typology. Findings attest to the plethora of diverse cladding media on physical structures on the Akoka campus. It further sheds light on the lexicological signification of Àkọ́kà as Ifá, justified in the conceptualisation and clarification of Ifáṣìfitì, as a university. The study concludes that it hopes its findings will provoke further scholarship on Akoka and structural cladding in particular.